Spectrum estimation using sequency-ordered complex hadamard transform (SCHT) - Goh, Jason Wee Kiong. (2012)
Assuming that the frequency of a signal is unknown to us, which method can we use to determine the frequency? The answer will be to use the spectrum estimation method. Spectrum estimation is a very useful tool that transform signal from the time domain representation to frequency domain representation. Analyzing the spectrum in the frequency domain will lead us to an answer on the unknown signal’s frequency.